Anti-thrombosis Effects and Mechanisms by Xueshuantong Capsule Under Different Flow Conditions - Han, Shuxian; Chen, Ying; Wang, Jinyu; Zhang, Qian; Han, Bing; Ge, Yimeng; Xiang, Yanhua; Liang, Rixin; Zhu, Xiaoxin; You, Yun; Liao, Fulong (Frontiers in Pharmacology, 2019)
Xueshuantong capsule (XST) is a patented traditional Chinese medicine used for the prevention and treatment of thrombosis. The molecular mechanism of XST anti-thrombosis effect through the cross-talk among the platelets/leukocytes, endothelial cells and flow shear stress was investigated. The Bioflux1000 system was used to generate two levels of shear stress: 0.1 and 0.9 Pa. Bioflux Metamorph microscopic imaging system was used to analyze the adhesion cell numbers. Protein expressions were detected by western blot assay and flow cytometry method. The flow-cytometry results showed that, under 0.1 Pa flow, XST decreased ADP induced platelets CD62p surface expression in a dose-dependent manner. Under 0.9 Pa flow, XST at the concentrations of 0.15 g·L-1 reduced the platelets activation by 29.5%; and ASA did not exhibit the inhibitory effect. XST showed similar efficiency on monocytes adhesion both under 0.1 and 0.9 Pa flow conditions, and the inhibition rate was 30.2% and 28.3% respectively. Under 0.9 Pa flow, the anti-adhesion effect of XST might be associated with the suppression of VE-cadherin and Cx43. Under 0.1 Pa, the inhibition on platelets and THP-1 adhesion by XST may be through decreasing VCAM-1 expression. Blood flow performs not only as drug transporter but also exerts its effects to influence pharmacodynamics of XST. Effects of XST inhibiting platelets activation and suppressing platelets/leukocytes adhesion to injured endothelial cells are not only dose-dependent, but also shear stress-dependent. The mechanic forces combined with traditional Chinese medicine may be used as the precision treatment for cardiovascular disease.